Pengaruh User-Generated Content (UGC) Tiktok terhadap Minat Beli Konsumen : pada UMKM Legendaris Es Krim Pokat Au di Tebing Tinggi - Alimul Hakim; Annisa Nurul Hidayah; Bobby Hartanto; Willy Cahyadi (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2026)
TikTok's rise as a dominant short-form video platform has created new channels through which User-Generated Content (UGC) influences consumer behavior. This study investigates the effect of TikTok UGC on purchase intention toward Es Krim Pokat Au, a heritage culinary micro-enterprise in Tebing Tinggi, North Sumatra—a context underrepresented in existing UGC literature dominated by fashion and cosmetic studies in metropolitan markets. A causal-quantitative design was adopted, with data collected from 96 purposively selected TikTok users who had been exposed to UGC content about this product. Instruments were validated using Pearson Product Moment (r table = 0.355; all items valid) and shown to be reliable (Cronbach's Alpha: X = 0.818, Y = 0.791). Residuals were normally distributed (Monte Carlo Sig. = 0.427 > 0.05). Simple linear regression via IBM SPSS 25 revealed a significant positive effect of UGC on purchase intention (β = 0.693; t = 9.380; p = 0.000 < 0.05; R² = 0.483). These findings confirm that authentic, visually appealing, and culturally relevant UGC serves as a cost-effective promotional mechanism for traditional culinary micro-enterprises targeting digital-native consumers.